Factors Needed to Establish Cross Border Economic Zones: Some Assessments for Cao Bang - Thu, Nguyen Anh; Huong, Vu Thanh (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2019)
In recent decades, border economic cooperation has developed under various forms. A cross-border economic zone (CBEZ) is a form that has been increasingly studied by academics as well as policymakers in Vietnam and neighbouring countries. This paper analizes the previously studied conditions to develop a CBEZ in the case of Lao Cai province so as to identify strengths and weaknesses and propose implications. It is found that in order to develop a CBEZ and to better faciliate trade and investment which is considered as an important chain to link with the market of China, Cao Bang province should focus on infrastructures, linkages and a harmonized mechanism of cooperation with China.